Effect of saturable absorber in 1.5 μm wafer-fused vertical cavity surface-emitting lasers. (December 2020) - Blokhin, S A; Bobrov, M A; Maleev, N A; Blokhin, A A; Vasyl'ev, A P; Kuzmenkov, A G; Ustinov, V M; Gladyshev, A G; Babichev, A V; Novikov, I I; Karachinsky, L Ya; Voropaev, K O; et al.
Abstract: The static characteristics of 1.5 μm wafer-fused VCSEL with the thin n ++ -InGaAs/p ++ -InGaAs/p ++ -InAlGaAs tunnel junction (TJ) were investigated. The devices with the 8 μm diameter of the buried tunnel junction (BTJ) demonstrate effective single-mode lasing. A rapid increase in the threshold current, accompanied by an abrupt change in the output optical power is observed for devices with BTJ-diameter less than 7 μm. The observed behavior can be explained by increasing in the overlap of the optical mode with the unpumped (passive) part of the active region, which leads to the additional optical absorption. On the one hand, since the high-order transverse modes have the higher optical losses due to larger overlap with the unpumped part of the active region, then lasing via fundamental mode is more preferable even at large size of BTJ region. On the other hand, the reduction of effective index step between the BTJ region and the regions outside BTJ (caused by using small TJ etching depth) and the lateral smoothing of the difference in the height of the surface relief after TJ regrowth results in the significant drop of the transverse optical confinement factor and rise of absorption. Moreover, the absorption effect can be also strongly enhanced by increasing the heatsink temperature due to decreasing in the gain-to-cavity detuning.